2015
DOI: 10.5603/kp.a2014.0240
|View full text |Cite
|
Sign up to set email alerts
|

The importance of electrocardiographic findings in the diagnosis of atrial septal defect

Abstract: Detection of RBBB, DTW, and crochetage R wave in superficial ECG may contribute to early detection in patients with ASD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 17 publications
1
18
2
1
Order By: Relevance
“…The ECG abnormality with the highest yield of abnormal TTE in our study was IRBBB. This finding on ECG suggests right‐sided volume overload, most commonly associated with the presence of an ASD . The odds of an abnormal TTE in an asymptomatic patient with IRBBB were approximately 10 times higher than in someone without IRBBB.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The ECG abnormality with the highest yield of abnormal TTE in our study was IRBBB. This finding on ECG suggests right‐sided volume overload, most commonly associated with the presence of an ASD . The odds of an abnormal TTE in an asymptomatic patient with IRBBB were approximately 10 times higher than in someone without IRBBB.…”
Section: Discussionmentioning
confidence: 96%
“…This finding on ECG suggests right-sided volume overload, most commonly associated with the presence of an ASD. 13 The odds of an abnormal TTE in an asymptomatic patient with IRBBB were approximately 10 times higher than in someone without IRBBB. It is important to note that interpretation of IRBBB has been suggested that LVH on ECG is more common in the African American population as compared to Caucasians.…”
Section: Re Sultsmentioning
confidence: 96%
“…Clínicamente, estos defectos pueden ser sospechados en casos de moderada a severa repercusión, cuando los pacientes presentan cuadros respiratorios recurrentes, escasa ganancia ponderal o hallazgos en la auscultación cardíaca (segundo ruido desdoblado ( 3 ) o soplo sistólico pulmonar ) . Dentro de las herramientas paraclínicas, el electrocardiograma se considera como un elemento que puede llevar a la sospecha de un defecto del septo interatrial, cuando presenta signos de sobrecarga de cavidades derechas (4) o alteraciones en la morfología del QRS o la onda T .…”
Section: Introductionunclassified
“…[ 1 ] Incomplete RBBB is due to delayed depolarization of the thickened right ventricular outflow tract and possibly right ventricular volume overload. [ 2 ] RSR’ pattern in lead V1 carries the specificity of 80%, sensitivity of 36.1%, positive predictive value of 14.7%, and negative predictive value of 92.9% for the diagnosis of ASD. Hence, incomplete RBBB alone is inadequate to diagnose ASD.…”
mentioning
confidence: 99%
“…used the defective T-wave pattern which was defined as “inverted or horizontal displacement of the proximal T-wave limb in the right precordial leads.”[ 9 ] Incomplete RBBB along with the presence of defective T-wave had 100% specificity and 87.1% sensitivity for the diagnosis of ASD. [ 2 9 ] These ECG findings can potentially help clinicians diagnose ASD and assess the risk of transient ischemic attack even before confirming the diagnosis on echocardiography.…”
mentioning
confidence: 99%